Gene Expression of Metalloproteinases and Endogenous Inhibitors in the Lamellae of Dairy Heifers With Oligofructose-Induced Laminitis - Ding, Jiafeng; Shi, Mingxian; Wang, Long; Qi, Dongdong; Tao, Ze; Hayat, Muhammad A.; Liu, Tao; Zhang, Jian-tao; Wang, Hongbin (Frontiers in Veterinary Science, 2020)
Bovine laminitis leads to huge economic losses and animal welfare problems in the dairy industry worldwide. Numerous studies suggested that several metalloproteinases (MPs) may play vital roles in the failure of epidermal attachment. To the best of our knowledge, the present study is the first to investigate and characterize the gene-level changes in distinct MPs and endogenous inhibitors using oligofructose (OF)-induced bovine laminitis model. The objective of this study was to determine aberrant MPs and related inhibitors of bovine laminitis in gene level, and to provide reasonable directions for the further protein-level research. Twelve normal Chinese Holstein dairy heifers were randomly divided into treatment group (n = 6) and control group (n = 6). The heifers in the treatment group were administered with OF solutions at a dose of 17 g/kg of body weight via a stomach tube. The heifers were then humanely euthanized when they met the criteria of bovine laminitis. The heifers in the control group were administered with deionized water at a dose of 2 L/100 kg of body weight. They humanely euthanized at 72 h. The gene expressions of MPs and endogenous inhibitors, namely, matrix metalloproteinases (MMPs), A disintegrin and metalloproteinases (ADAMs), and A disintegrin and metalloproteinase with thrombospondin motifs (ADAMTs), and tissue inhibitors of metalloproteinases (TIMPs) in the lamellae from two groups were determined via real-time quantitative PCR. The gene expressions of MMP-2, MMP-9, ADAMTS-4, and ADAMTS-5 significantly increased (P < 0.05), whereas that of TIMP-2 significantly decreased (P < 0.05) in the treatment group relative to the control group. No significant difference was found in the gene expressions of ADAM-10, ADAM-17, TIMP-1, and TIMP-3. These results indicated that the gene-level imbalanced condition of MPs and their TIMPs may be the basic cause for the failure of epidermal attachment. At the same time, more detailed protein-level studies would be needed to further clarify the roles of MPs and TIMPs in the pathogenesis of bovine laminitis, especially to MMP-2, MMP-9, ADAMTS-4, ADAMTS-5, TIMP-2 as well as related substrates (e.g., aggrecan and versican).